Eco-friendly approach for preparation of water-based superhydrophobic silica aerogels via ambient pressure drying - Xiaoling Yuan; Lihui Xu; Hong Pan; Yong Shen; Liming Wang; Mingrui Xie (Materials Research Express, 2021)
In this work, superhydrophobic methyltrimethoxysilane (MTMS)-based silica aerogels were fabricated via water-based sol–gel reaction by ambient pressure drying (APD) method in the presence of surfactant. The structure, morphology, and hydrophobic properties of the obtained silica aerogel were characterized by scanning electron microscopy (SEM), Brunauer–Emmett–Teller (BET) methods, X-ray diffractometer (XRD), and water contact angle measurement. The effects of the concentration of MTMS, the pH value of the solution, and the amount of surfactant cetyltrimethylammonium bromide (CTAB) on properties of silica aerogels were investigated, respectively. Increasing the concentration of MTMS to a great extent resulted in higher density and lower porosity of silica aerogel. Alkali catalyst was an extremely crucial factor for preparing silica aerogels. With the increase of the pH value from 7.5 to 10 the gelation time of the prepared aerogels was observed to decrease from 40 min to 2 min, and the shrinkage of aerogel sample decreased from 15.5% to 3.5%. The skeleton structure of the prepared silica aerogel gradually transformed from coarsened spherical to continuous irregularity finer structures with the increased concentration of CTAB. In addition, the prepared silica aerogel showed outstanding anti-adhesion property and superhydrophobic ability with a water contact angle (WCA) of 160.6 ± 1.3°.